Can Concept Mapping Facilitate Verbal Divergent Thinking?. Issue 4 (1st October 2020) - Xu, Xiaobo; Pang, Weiguo
ABSTRACT: It is well established that creativity can be stimulated by expanding the breadth of knowledge activation. In addition, some researchers have proposed that concept mapping can stimulate individuals into more flexible thinking processes. Based on the literature, three studies were conducted in the present research to systematically investigate whether concept mapping as a way of knowledge activation can increase individual performance in a widely used verbal divergent thinking task, the alternative uses task (AUT). As a first step, Study 1 investigated the relationship between individuals' concept mapping ability and their AUT performance. Then, by means of experimental manipulation, Study 2 examined whether cross-links were an important element through which concept mapping facilitated AUT performance. Study 3 further examined whether dissociative ability (as an indicator of breadth of knowledge activation) mediated the relationship between cross-links and AUT performance. Taken together, the results indicated: 1) among the four indices of concept mapping ability (propositions, hierarchies, cross-links, and examples), propositions and cross-links showed positive associations with AUT performance; 2) cross-links were an important element through which concept mapping priming facilitated AUT performance; 3) dissociative ability fully mediated the relationship between cross-links and AUT fluency. Implications and future directions were discussed in detail.